Answer:-1/32
Step-by-step explanation:
First term=a=1024
Common ratio=r=-512/1024
r=-1/2
Using them formula
Tn=a x r^(n-1)
T16=1024 x (-1/2)^(16-1)
T16=1024 x (-1/2)^15
T16=1024 x -1/32768
T16=-1024/32768
T16=-1/32
To land on 0 the number would need to end with a .5 or .0 since that is the only way .0 can occur with counting down by.5( half)
Step-by-step explanation:
G = (z-s) ÷ r
G × r = (z- s)
Gr + s = z
Answer:
11
3Step-by-step explanation:
Given
3(x - 1)² + 2x - 7 ← substitute x = 3 into the expression
= 3(3 - 1)² + 2(3) - 7
= 3(2)² + 6 - 7
= 3(4) - 1
= 12 - 1
= 11
Answer:
7/10
Step-by-step explanation:
I've attached an image on how you can use the diagram they gave you.
If you color in 7/10s and 7/12s you'll notice that 7/10s is greater.
This is because 1/10 of the whole is greater than 1/12 of the whole.
For 1/10, the whole is being divided into 10, so it equals 0.1.
On the other hand, in 1/12, the whole is being divided by 12, so a part equals 0.083
0.1 is greater than 0.083, so 7 of 0.1 is greater than 7 of 0.083